Illuminating the nightlife of two Neotropical nightjars: vocal behavior over a year and monitoring recommendations. Issue 5 (2nd September 2020) - Pérez-Granados, Cristian; Schuchmann, Karl-L.
Abstract : The ecology of tropical wildlife remains unknown for most nocturnal species owing to difficulties in performing night surveys. To improve our understanding of the ecology of nocturnal tropical birds, we monitored the calling activity of two Neotropical nightjars, the Little nightjar ( Setopagis parvula ) and the Common pauraque ( Nyctidromus albicollis ), over an annual cycle at four sites in the Brazilian Pantanal. The calling activity of both species was restricted to the nocturnal period and showed peaks of activity just before dawn and just after dusk. The Little nightjar was detected from early June to late January owing to the migratory habits of the species, while the Pauraque was detected throughout the year. Our results suggest that the breeding season of both species starts in August, and the nesting phase probably takes place in September at the end of the dry season. This might be related to the typical increase in arthropod abundance after the first rains in tropical habitats with seasonal rainfall. Future surveys of these species should be performed in the last fortnight of August at 5 am, a period during which the calling activity of both nightjars was maximum. Autonomous sound recorders should be left in the field for a minimum of 9 days to record a reliable vocal activity rate. Acoustic monitoring, coupled with automated signal recognition, has proven to be a useful tool for monitoring tropical nightjars and may be useful to increase our knowledge about the ecology of other nocturnal tropical species.